Early hydroxychloroquine but not chloroquine use reduces ICU admission in COVID-19 patients. (December 2020) - Lammers, A.J.J.; Brohet, R.M.; Theunissen, R.E.P.; Koster, C.; Rood, R.; Verhagen, D.W.M.; Brinkman, K.; Hassing, R.J.; Dofferhoff, A.; el Moussaoui, R.; Hermanides, G.; Ellerbroek, J.; et al.
Highlights: Following a global push for the use of hydroxychloroquine and chloroquine, there is ongoing discussion about the effectivity of these drugs. The findings of this observational study provide crucial data on a potential protective effect of hydroxychloroquine in non-ICU, hospitalized, COVID-19 patients. Early treatment with HCQ on the first day of admission is associated with a 53% reduction in risk of transfer to the ICU for mechanical ventilation. This protective effect was not observed for chloroquine; therefore, these drugs cannot be regarded as interchangeable. Abstract: Background: The global push for the use of hydroxychloroquine (HCQ) and chloroquine (CQ) against COVID-19 has resulted in an ongoing discussion about the effectivity and toxicity of these drugs. Recent studies report no effect of (H)CQ on 28-day mortality. We investigated the effect of HCQ and CQ in hospitalized patients on the non-ICU COVID-ward. Methods: A nationwide, observational cohort study was performed in The Netherlands. Hospitals were given the opportunity to decide independently on the use of three different COVID-19 treatment strategies: HCQ, CQ, or no treatment. We compared the outcomes between these groups. The primary outcomes were 1) death on the COVID-19 ward, and 2) transfer to the intensive care unit (ICU). Results: The analysis included 1064 patients from 14 hospitals: 566 patients received treatment with either HCQ ( n = 189) or CQ ( n = 377), and 498 patients received no treatment. In a multivariate propensity-matched weighted competing regression analysis, there was no significant effect of (H)CQ on mortality on the COVID ward. However, HCQ was associated with a significantly decreased risk of transfer to the ICU (hazard ratio (HR) = 0.47, 95% CI = 0.27–0.82, p = 0.008) when compared with controls. This effect was not found in the CQ group (HR = 0.80, 95% CI = 0.55–1.15, p = 0.207), and remained significant after competing risk analysis. Conclusion: The results of this observational study demonstrate a lack of effect of (H)CQ on non-ICU mortality. However, we show that the use of HCQ — but not CQ — is associated with a 53% reduction in risk of transfer of COVID-19 patients from the regular ward to the ICU. Recent prospective studies have reported on 28-day, all-cause mortality only; therefore, additional prospective data on the early effects of HCQ in preventing transfer to the ICU are still needed.